Philippine Agricultural Research and Development: Issues and Policy Implications - Cristina C. David (Philippine Institute for Development Studies (PIDS), 1995)
Despite the major contribution of agricultural sector to the Philippine economy, it has been performing dismally since the 1980s. This has been attributed to limited technological progress, inefficiencies in resource allocation and limited infrastructure development. This paper focuses on the reasons behind the limited technological progress in the Philippines. In particular, it investigates the policy actions that should be undertaken to moderate the underfunding of agricultural research and extension and the associated institutional weaknesses in the sector.
Keywords: 330; agricultural technology; agriculture sector; research; technological innovation